Education Interventions to Improve Knowledge, Beliefs, Intentions and Practices with Respect to Dietary Supplements and Doping Substances: A Narrative Review - Jana Daher (MDPI AG, 2021)
The misuse of dietary supplements and doping substances is commonly associated with toxicity, nutritional imbalances, and health and psychological consequences. This is alarming especially in light of the increasing prevalence of the use of dietary supplements and doping, particularly among young adults including athletes. There is evidence that education interventions can lead to improved knowledge, intentions, and practices. However, no review has summarized and evaluated the effectiveness of such interventions. The aim of this article is to review the characteristics, contents and effects of education interventions that were designed and implemented to improve knowledge, attitudes, beliefs and intentions with respect to the use of dietary supplements and doping agents in different populations. PubMed, Scopus, CINAHL, PsycInfo and Google Scholar were searched for English-language education interventions targeting dietary supplements and doping substances. A total of 20 articles were identified and have generally provided consistent findings. Most interventions reported a significant improvement in knowledge on dietary supplements and doping agents. Unfortunately, the heavy reliance on self-reported assessment tools limits the validity of these interventions, with almost all articles targeting athletes and adolescents.